Investigation of Hydrosphere Contamination by Untreated Landfill Infiltrates and Cleaning Agents to Improve Environmental Protection - Zinaida M. Nazarova (Polish Society of Ecological Engineering (PTIE), 2022)
Landfill infiltrates cause contamination of surface, ground, and groundwater. To minimize this danger it is necessary to implement technical measures for collecting and cleaning infiltrates The subject of the study is the processes of biological treatment of landfill infiltrates in aerobic lagoons and urban wastewater treatment plants. The content of nutrients necessary for plants in wastewater sediments makes it possible to use them as organic fertilizer. The fertilizing value is largely determined not only by the content of nitrogen, phosphorus, and potassium in them but also by the microelements necessary for plants - boron, molybdenum, manganese, zinc, magnesium, iodine, copper, iron, sulfur, etc. It was found that compacted excess activated sludge is a valuable complex mineral fertilizer with a high content of N and P. The possibility of converting sediment into a complex fertilizer by neutralizing wastewater sludge under biosulfidogenesis conditions during dissimilation reduction of poorly soluble sulfates is considered. The results obtained are consistent with experimental data corresponding to the dynamics of the biogenic gas released from the bioreactor. By the nature of changes in the kinetics of biogenic carbon disulfide yield, changes in the acetate concentration and the rate of sulfate absorption, it is possible to predict the process of biosulfidogenesis and find the most optimal parameters of the system. This indicates the possibility of its use in biotechnology for the neutralization of wastewater sludge with the production of a complex organometal fertilizer